(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2015)
An 18 years old girl with history of ingestion of unquantified amount of insecticide was admitted in the intensive care unit with unconsciousness, hurried respiration. It was diagnosed as a case of organo-phosphate compound poisoning and treated accordingly. After the crisis over, the patient developed respiratory failure. The patient had no fever, no change in X-ray chest or blood count. It is now recognized as a complication of organo-phosphate compound poisoning named Intermediate Syndrome. Manifestations in this particular case is that only the respiratory muscles were involved and repeated respiratory insufficiency developed which was overcome by positive pressure ventilation. JCMCTA 2015 ; 26 (1) : 52-54